Rangeland evaluation in relation to pastoralists perceptions in the middle Awash valley of Ethiopia - Gedda, Abule Ebro (University of the Free State, 2003)
Pastoralism is the most dominant land use form in the arid rangelands of Sub- Saharan Africa in which Ethiopia is not an exception. However, in Ethiopia and elsewhere, rangeland-based life-styles are in difficulty with the rangeland environment under threat because of both external and internal constraints. The spatial variability of the annual rainfall in these areas also has an affect on the pastoralists livelihood. Accordingly, four studies were undertaken in two neighbouring districts occupied by pastoralists of different ethnic groups living in the middle Awash valley of Ethiopia with the objective of evaluating the condition of the rangelands, which was related to the perception of the pastoralists in order to come up with possible recommendations to minimize further degradation. The pastoralists perceptions of the rangeland resource were studied through group discussions and by using a structured questionnaire where each household was taken as a unit of analysis (90 households from Oromo living in Kereyu-Fantale district and 55 households from Mar living in Awash-Fantale district). The data was analysed using Statistical Package for the Social Sciences (SPSS). The result showed that the average family size per household was about 6.74, with nearly 80% of the people without any kind of education. The main source of income for both pastoral groups was from the sale of animals. The second source of income to the Oromo and Afar pastoralists was from the sale of crops and milk and milk by-products, respectively. Both pastoral groups reported that woody species like Cryptostegia grandiflora, Capparis fascicularis, Erythrina abyssinica and Flueggea virosa) and herbaceous species like Tribulus terrestris, Tephrosia subtriflora and Cynodo are sources of poisons which affect their livestock production. Ninety seven and 3% of the Oromo respondents use Cymbopogon commutatus and Chrysopogon plumulosus for house roofing respectively, while 38.1%, 23.0%, 10.6% and 28.3% of the Afar pastoralists use C. commutatus, C. exacavatus, Enterpogon and Sporobolus ioclados, respectively for a similar purpose. Seventy six percent of the Oromo and 77 % of the Afar respondents do not harvest grasses from the rangelands and the primary use of woody plants in both pastoral groups was for livestock feeding. It was indicated that the grazing lands were bush encroached notably with Acacia senegal, A. nubica and Prosopis juliflora (Awash-Fantale district only) and the condition of the rangeland to be in poor condition. None of the Afars and only 12% of the Oromo pastoralists had private grazing lands. The majority of the respondents chose to continue with communal type of ownership in the grazing lands and a shortage of water was a critical constraint to the Oromo pastoralists. There is a critical shortage of livestock feed during the dry season and the first measure taken to solve feed shortage is migration. Unfortunately, 90% of the Oromo and 60% of the Afar respondents replied that migration is a bad practise. The Afar pastoralists (cattle = 20; sheep = 12; goats = 26; Camels = 15) had a higher number of livestock owned per household than the Oromo pastoralis (cattle = 10; sheep = 8; Goats = Il; Camels = 5). Rangeland condition in terms of grass, browse and soil parameter was studied at Il sites in Awash- Fantale district and 10 sites iri Kereyu -Fantale district using techniques and/or methods mostly developed in South Africa. Grazing and browsing capacities were also calculated for each of the rangeland sites. The most dominant grass species-in the study districts was Chrysopogon plumulosus followed by different species of Sporobolus. The percentage bare ground as estimated by the point method varied from 0.33 to 10.79 with a mean value of 5.27. The basal cover in both districts was low, averaging 3.35%. The DM yield of the grass ranged between 168.52 kg ha" to 832 kg ha-I. The grazing capacity varied from as low as 54.14 ha LSU-I to as high as 7.06 ha LSUI. The results of the evapotranspiration tree equivalent (ETTE ha") showed that the study districts were bush encroached with A. senegal, A. nubica and P. juliflora. In both districts, the browse production (total leaf DM) ranged from as low as 194 kg ha" to 3 311 kg ha-I, with most of the leaf dry mass found above the height of 1.5 m. In both districts, the highest browsing capacity (ha BU-I) was contributed by A. senegal and A. nubica. The condition of the communal grazing lands was also assessed m relation to benchmark sites. Basal cover and the DM yield of grasses was higher in the benchmark sites (basal cover= 5.3% and DM yield of grasses = 985.7 kg ha") than the sample sites (basal cover = 3.3% and DM yield of grasses = 447.2 kg ha"), which indicated that given proper management, there is ample room to improve the grazing capacity of the rangelands. With the objective of studying the effects of tree species' on grass species composition, yield and some soil parameters under different grazing gradients (light, medium and heavy) in two sub-habitats (under canopy and open grassland), two tree species (Acacia tortilis and Balanites aegyptica) were identified. The data was analysed using DECORANA and SAS (Statistical Analysis System). The results showed that the grass species found at the heavily grazed sites were mostly annuals and less desirable species. The major difference between the medium and lightly grazed site in grass species composition was the presence of Panicum maximum under the canopy of trees in lightly grazed condition. The DM yield of grass improved substantially as the grazing intensity decreased (heavy = 31l. 9 kg ha", medium = 1 607 kg ha-I and light = 2 737.5 kg ha"). At the medium and lightly grazed sites, the DM yield of grass was higher (P<0.001) under tree canopies than the corresponding open grasslands. Soil nutrient status increased as the grazing pressure decreased from heavy to light grazing. Electrical conductance, percentage nitrogen and organic carbon increased (P<0.01) under tree canopies compared to the corresponding open grasslands whereas they decreased with an increase in the depth. of soil. In conclusion, all studies with different objectives and arguments clearly indicate that the condition of the rangelands IS poor, requiring careful and participatory interventions. Future studies need to distinguish between climate and man-made droughts although droughts are a normal phenomenon in these drier areas. Rangelands in poor condition increase the intensity and frequency of climatic droughts.
Thesis (Ph.D. (Animal, Wildlife and Grassland Sciences))-- University of the Free State, 2003
Keywords: Range management -- Ethiopia -- Awash River Valley; Rangelands -- Ethiopia -- Awash River Valley